Entrepreneurial Marketing in the Era of Digital Transformation: A Systematic Literature Review on Social Media, Digital Capabilities, and MSME Performance - Sintia Wulandari; Farida Febriati (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Digital transformation has brought fundamental changes to marketing practices, particularly for micro, small, and medium enterprises (MSMEs) that increasingly rely on digital technologies to develop their businesses. Entrepreneurial Marketing (EM), which emphasizes innovation, proactiveness, creativity, and customer orientation, has undergone a significant shift when combined with the use of social media, e-commerce, and other digital capabilities. This study aims to analyze how EM practices have evolved within the context of digital transformation through a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. The search process was conducted using the Scopus database with a combination of the keywords “entrepreneurial marketing” and terms related to digitalization. From the screening process, seven articles met the inclusion criteria and were examined in depth using narrative–thematic synthesis techniques. Overall, this study reveals that the success of EM in the digital era depends heavily on the integration of technology, content creativity, data utilization, and adaptation to changes in digital consumer behavior. The findings of this SLR offer theoretical contributions to the development of next-generation EM models and provide future research agendas related to EM and digitalization within the MSME context.